An investigation into the trends and patterns of requests for proposals for Employee Assistance Programmes (EAPs) from ICAS Southern Africa - Terblanche, Lourie (University of Pretoria, 2017)
Mini Dissertation (MSocSci)--University of Pretoria, 2017.